Network and Experimental Pharmacology to Decode the Action of Wendan Decoction Against Generalized Anxiety Disorder - Jin Q; Li J; Chen GY; Wu ZY; Liu XY; Liu Y; Chen L; Wu XY; Liu Y; Zhao X; Song YH (Dove Medical Press, 2022)
Qi Jin1 *, Jie Li2 *, Guang-Yao Chen1 *, Zi-Yu Wu,3 Xiao-Yu Liu,2 Yi Liu,4 Lin Chen,5 Xin-Yi Wu,5 Yan Liu,2 Xin Zhao,2 Yue-Han Song2 1Graduate School, Beijing University of Chinese Medicine, Beijing, 100029, People's Republic of China; 2School of Traditional Chinese Medicine, Beijing University of Chinese Medicine, Beijing, 100029, People's Republic of China; 3Dongzhimen Hospital, Beijing University of Chinese Medicine, Beijing, 100007, People's Republic of China; 4Humanities School, Beijing University of Chinese Medicine, Beijing, 100029, People's Republic of China; 5Qihuang School, Beijing University of Chinese Medicine, Beijing, 100029, People's Republic of China*These authors contributed equally to this workCorrespondence: Xin Zhao; Yue-Han Song, Email zhaoyyyx@sohu.com; songyuehan1981@126.comObjective: The mechanism of Wendan Decoction (WDD) against Generalized Anxiety Disorder (GAD) was predicted by network pharmacology and validated by in vivo and in vitro experiments.Methods: The targets of WDD for the treatment of GAD were obtained by a search of online databases. Further, PPI network and KEGG enrichment were used to identify the key targets and pathways. Ultimately, these key targets and pathways were validated by in vivo experiments on GAD mice modeled by repeated restraint stress (RRS) and in vitro experiments on inflammatory factor stimulated BV-2 cells.Results: Through searching the databases, the 137 ingredients of WDD that correspond to 938 targets and 4794 targets related to GAD were identified. Among them, 569 overlapping targets were considered as the therapeutic targets of WDD for GAD. PPI analysis showed that the inflammation-related proteins IL-6, TNF, SRC and AKT1 were the key targets, and KEGG enrichment suggested that PI3K/AKT and MAPK signaling pathways were key pathways of WDD in the treatment of GAD. In vivo experiments, RRS mice exhibited abnormality in behavioristics in open field test (OFT) and elevated plus maze (EPM) and increases in serum corticosterone and the percentage of lymphocytes positive for IL-6 in peripheral blood. These abnormal changes can be reversed by WDD and the positive control drug paroxetine. In vitro experiments, WDD can inhibit IL-6 induced activation of PI3K/AKT and MAPK signaling pathways in BV2 cells, and suppress the ensuing release of inflammatory factors TNF-α, IL-1β and PGE2, and showed a dose-dependent effect.Conclusion: WDD is able to resist GAD by relieving inflammatory response in peripheral and central system.Keywords: Wendan Decoction, Generalized Anxiety Disorder, network pharmacology, Interleukin-6, PI3K/AKT signaling pathway, MAPK signaling pathway